The Multi-feature Classification of Armenian Dialects - HANANYAN, GAGHTUHI (Bulletin of Yerevan University B: Philology, 2021)
In the seventies of the previous century, academician G. Jahukyan put forward the principle of multi-feature classification of Armenian dialects. In contrast to mono-feature classification, the given approach defines exact mathematical indices which not only demarcate the subordination limits of dialectal units but also reveal the interrelationships of Armenian dialects. The intermediary chains are distinguished which express transitional features. As the problem of the Armenian dialects is complex and diverse, we can specify the choice and number of about 100 characters. The main principles of multi-feature classification open new horizons not only for the research of the Armenian dialects but for the studies of the Armenian language as well.